Effectiveness of integrative structural family therapy and double ABCX model on marital adjustment and parenting stress among parents of children with autism: randomized controlled trial - AlHorany, Ahmed Kamel; Hassan, Siti Aishah; Juhari, Rumaya; Aljaberi, Musheer A. (Routledge, 2024)
Marital adjustment is an important predictor of coping with stress among parents of children with autism spectrum disorder (ASD). A randomized controlled trial conducted on 60 parents of children with ASD showed that integrative SFT and double ABCX therapy, conducted over ten sessions of multiple family therapy in group counseling for five weeks and a one-month follow-up at special needs children’s centers in Jordan, resulted in a 48% increase in marital adjustment and a 34% reduction in parenting stress. These therapies significantly improved the well-being of parents of children with autism, while the control group did not.